Os poderes processuais que vêm sendo conferidos ao amicus curiae em sua trajetória nas ações de controle de constitucionalidade julgadas pelo Supremo Tribunal Federal - Sampaio, Ricardo Alves (2009)
Brazil is a country of rigid constitution. Although the responsibility for drafting the laws belong, as a rule, to the parliamentarians who are elected directly by people, the judges, unlike those who are not elected, sometimes are submitted to public tender of evidence and securities or are indicated by political criterion , as the composition of the high courts that have the power to declare laws unconstitutional, nullifying them. Thus, there is a deficiency in the performance of the democratic constitutional jurisdiction. On this track, the doctrine suggests greater legitimacy as desirable in the interpretation made by the judges to exercise the control of constitutionality and reveal a mechanism of connection between the popular will and judgments of the intervention of civil society in the processes through Amicus curiae. The research examines the figure of the Amicus curiae in its trajectory inside concentrated control of constitutionality in Brazil, since the days when it was accepted informally, through its positive in Law 9868/99, until the present time in which the Supreme Court has granted other prerogatives that are under the law, showing the current phase which involves advancement of the judicial precedent in law